China : International Trade and WTO Accession - Blancher, Nicolas (IMF Working Papers; Working Paper ;, 2004)
China's increasing integration with the global economy has contributed to sustained growth in international trade. Its exports have become more diversified, and greater penetration of industrial country markets has been accompanied by a surge in China's imports from all regions-especially Asia, where China plays an increasingly central role in regional specialization. Tariff reforms have been implemented in China since the 1980s; and, with its recent WTO accession, China has committed itself to additional reforms that are farreaching and challenging. Sustained implementation of these commitments would further deepen China's international integration and generate benefits for most partner countries.